Analysis of Quality Control of Emulsion Flavor Products Based on Stability Properties in Product Applications at PT. XYZ flavours - Nadya Villarasty; Bambang Dwi Argo; Rini Yulianingsih (Contributions of Central Research Institute for Agriculture, 2022)
PT. Flavors XYZ is one of the multinational company in producing flavors and fragrances as raw materials for consumer goods production. PT. Flavors XYZ producing several types of flavors including liquid flavors, powder flavors, and tobacco flavors which are used as ingredients in food, beverage, and cigarette industry. Quality control and assurance is a feature that affects products to be well received by consumers. Quality control and assurance is necessary to ensure products meet the quality standard. Emulsion flavors is one type of flavor produced by this company. The instability is commonly observed in emulsion flavors products, hence the quality control division conducts the surveillance for several days (5 to 7 days) to ensure the product is stable until the expiry date when applied to beverage products. The corrective action which is conducted in emulsion flavors production refers to analysis of cause-effect diagram by detecting the causes of deviations that may affect the quality of products. Those factors including machine, man, material, method, and environment. The methods which are used for fixing problems including machine reparation, re-adjust the configuration settings, and conduct the raw materials replacement of emulsifier which is used in orange emulsion type JJ.